Effects of badminton training on some physical parameters in badminton players aged 10 to 12 years - Samet Aktas; Faruk Guven; Yusuf Er (Türk Spor ve Egzersiz Dergisi)
This study aimed to determine some physical parameters of badminton players in the ages of 10-12. Fifteen badminton players in 10-12 years old volunteered to participate. The players continued their badminton training for 8 weeks. After and before the 8 week training, their 15 m speed, vertical jump, standing broad jump, hand grip strength and flexibility tests were conducted. To analyses the data, paired t-test was used to compare the pre- and post-test tests. After the badminton training of the 8 weeks, subjects’ vertical jump, the hand grip strenght (right hand) and flexibility performances increased significantly (p lt;0.05). There was no significant difference in standing broad jump, 15 m speed and lefht hand-grip strength between pre- and post-test (p gt;0.05). As a result, it can be said that the badminton training of an 8-week might improve vertical jump, flexibility and hand grip strength in 10-12 years old badminton players. Howerever, the training may not have any effect on their 15 m speed and standing broad jump performance.